MicroRNA profile of immune response in gills of zebrafish (Danio rerio) upon Staphylococcus aureus infection. Issue 87 (April 2019) - Zhang, Qi-Lin; Dong, Zhi-Xiang; Luo, Zhi-Wen; Jiao, Yun-Jian; Guo, Jun; Deng, Xian-Yu; Wang, Feng; Chen, Jun-Yuan; Lin, Lian-Bing
Abstract: The gills of fish are large mucosal surfaces that are very important portals for pathogen entry. Investigations have shown that microRNAs (miRNAs) are key regulators of immune response to bacterial infections in the gills of fish; however, how miRNA expression changes in response to infection by Gram-positive bacteria remains largely unknown. To further investigate the immunological role of miRNAs in fish gills under pathogen stress induced by Gram-positive bacterial infection, this study investigated Staphylococcus aureus ( SA )-induced changes in the miRNAs levels in gills of adult zebrafish ( Danio rerio ). miRNA microarrays were used to analyze expression profiles of known miRNA in the gills of zebrafish in response to SA infection and compared these to uninfected control fish. A total of 30 differentially expressed miRNAs (DEMs) were identified. Target genes likely regulated by DEMs were predicted, and functional enrichment analyses were performed. The results indicated that DEM targets were primarily involved in innate immune processes, apoptosis, defense responses, and antibacterial responses. Pathways involving bacterial infection, innate immunity, metabolic process, disease, and apoptosis were mediated by DEMs. Furthermore, real-time quantitative PCR experiments for nine key SA -responsive DEMs that regulated the " SA infection" pathway validated the accuracy of microarray results. Dynamic variations in gene expression were surveyed in detail for these key SA -responsive DEMs for PBS control and at 6, 12, 24, and 48 h after SA challenge in detail. This study provides novel insight into the mechanisms underlying the miRNA regulation during the SA -induced immune response in zebrafish gills, and provides basic knowledge on the innate immune response against Gram-positive bacterial infection in bony fish. Highlights: DEM profiling was analyzed in zebrafish gills between control and SA -treated groups. 30 differentially expressed miRNAs (DEMs) were identified after SA challenge. The experiment of qRT-PCR validated the accuracy of miRNA microarrays. This is the first time to investigate antibacterial response of mass miRNA expression in zebrafish gills.